Public Relations Management in Enhancing Branding and Quality at SD Negeri 1 Rensing - Romi Oriza; Hamzani Badri (Journal of Scientific Studies and Multidisciplinary Research, 2025)
In today’s competitive educational environment, strategic public relations (PR) play a vital role in shaping school branding and enhancing institutional quality. This study investigates the implementation, challenges, and effectiveness of PR management at SD Negeri 1 Rensing, a public elementary school in East Lombok, Indonesia. Using a qualitative descriptive approach, the research involved interviews, field observations, and documentation analysis, conducted between June and July 2025. The findings reveal that PR activities, though not professionally structured, are actively carried out through religious and community events, WhatsApp-based parent communication, and limited use of social media. Key challenges identified include the absence of trained PR personnel, insufficient ICT infrastructure, and low parental digital literacy. Despite these limitations, PR efforts have led to increased enrollment—including students from outside the school zone—improved academic and non-academic performance, and stronger community involvement. The study contributes to the field by offering a rural perspective on school PR practices, often underrepresented in literature, and emphasizes the role of informal, community-driven communication strategies. It concludes that even in resource-constrained settings, effective PR can significantly support school branding and quality improvement.